The fault in our stars - Green, John (New York : Dutton Books, 2012)
Sixteen-year-old Hazel, a stage IV thyroid cancer patient, has accepted her terminal diagnosis until a chance meeting with a boy at cancer support group forces her to reexamine her perspective on love, loss, and life.
Keywords: Cancer in adolescence -- Fiction; Friendship -- Fiction; Love stories